Penggunaan Teknologi Informasi Untuk Mengelola Data Masjid Al-Jihad – Pematangsiantar - Indra Gunawan Indra; Sumarno; Heru Satria Tambunan (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
Every activities carried out by the Board of Mosques has been regulated and set forth in the Regulation of the Minister of Religious Affairs No. 54 of 2006 concerning a form of organizational structure of organizational management and work procedures of “Badan Kesejahteraan Masjid” (BKM). With the regulation that has been set by the Government, then every mosque jama'ah is willing and ready to accept the mandate and duties directed by the Government in terms of the management of the Mosque. For the processing of mosque data, it is time to utilize information and technology so that data management and information delivery about the Mosque can be done quickly and appropriately. In order for the data collection to be done easily, it is necessary to build information and technology facilities and infrastructure through internet services for faster and more precise access to information. So with this service, to provide Information Sharing about mosques to Jama'ah Mosque can be done from anywhere and anytime as long as the internet connection network is connected with smarthphone media and Computers.